A Decision Aid May Offer Liability Protection for a Bad Obstetrical Outcome: Results of Mock Trials. Issue 4 (December 2018) - Brodney, Suzanne; Wescott, Pamela H.; Moulton, Benjamin W.; Hartmann, Katherine; Chang, Yuchiao; Barry, Michael J.
The objective of this study is to evaluate if use of a patient decision aid (PDA), when choosing between a repeat cesarean or a trial of labor after a cesarean (TOLAC), reduces medical liability exposure. The authors conclude that use of a PDA conferred liability protection when potential jurors were presented with a hypothetical malpractice claim against an obstetrician following a TOLAC.